Android Based Information System Modelling: Case Study of Building Materials Sales - Syafariani, R Fenny; Hayati, Euis Neni (International Journal of Research and Applied Technology (INJURATECH), 2024)
When a pandemic occurs, people are forced to carry out Large-Scale Social Restrictions (LSSR) set by the government. Therefore, everything must be done online to break in the chain of spreading the virus. In reality, many people have smartphones that are connected to the internet and companies took that fact as an advantage. One of the companies is WS supplier that can order building materials through an online application. The purpose of this study is to design an Android-based building material purchase application model. The method used in this research is the descriptive analysis method by making observations at the WS Supplier business premises as the object of research. In this application, the modelling used a project-oriented approach and a prototype system development method. The results showed that this application could help marketing and facilitate online-based ordering. With this application model, it is hoped that it can increase sales in the building materials sector so that it can continue to operate during a pandemic and post-pandemic. This research has produced a prototype design in the form of an application that can be used as media in a business field to increase sales amid the Covid-19 pandemic. With this research, it is hoped that it can be beneficial both in the same field and in others to help the economy of the community during a pandemic by adhering to health protocol. The WS Supplier application is designed to be a model application for building material service providers to make promotional and ordering materials accessible to customers via smartphone